In vitro effect of 4-pentylphenol and 3-methyl-4-nitrophenol on murine splenic lymphocyte populations and cytokine/granzyme production. (3rd July 2016) - Yang, Lubing; Ma, Sihui; Wan, Yifang; Duan, Shuqi; Ye, Siyan; Du, Shengjie; Ruan, Xinwei; Sheng, Xia; Weng, Qiang; Taya, Kazuyoshi; Xu, Meiyu
Abstract: Gasoline exhaust particles (GEP) and diesel exhaust particles (DEP) are considered to be some of the most important air pollutants. Among the many constituents in these pollutant particles, 4-pentylphenol (PP) and 3-methyl-4-nitrophenol (PNMC) are considered important phenolics in GEP and DEP, respectively. The aim of this study was to investigate the effect of in vitro exposure to commercially-supplied PP and PNMC on populations of, and production of interleukin (IL)-2, IL-4 and granzyme-B by, mouse splenic lymphocytes. After in vitro exposure to PP or PNMC for 48 h, splenocyte viability was measured, cell phenotypes, e.g. B-cell (CD19), T-cells (CD3), T-cell subsets (CD4 and CD8), were quantified by flow cytometry and production of IL-2, IL-4 and granzyme-B was assessed via ELISA. The oxidative toxicity of PP and PNMC toward the splenocytes was also evaluated using measures of hydroxyl radical and malondiadehyde production and changes in glutathione peroxidase and superoxide dismutase activities. Results showed that in vitro exposure to PP and PNMC inhibited splenic cell parameters in a dose-related manner. Exposure to PP and PNMC decreased splenic T-lymphocyte populations and splenocyte production of cytokines and granzyme B, as well as induced oxidative stress in the splenocytes. The results also showed that the percentages of CD3 + T-cells overall and of CD4 + and CD8 + T-cells therein, among exposed splenocytes, were reduced; neither compound appeared to affect levels of CD19 + B-cells. Overall, the suppressive effects of PP were stronger than PNMC. The data here provide support for the proposal that PP-/PNMC-induced toxicity in splenocytes may be due at least in part to oxidative damage and that PP and PNMC – as components of GEP and DEP – might significantly impact on splenic T-cell formation/release of cytokines/granzymes in situ .